2020
DOI: 10.1111/bju.15290
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of stent‐associated morbidity by minimizing stent material: a prospective, randomized, single‐blind superiority trial assessing a customized ‘suture stent’

Abstract: To compare a customized 'suture stent' with a standard ureteric stent regarding stent-related symptoms, safety and efficacy. Materials and MethodsPatients with urolithiasis located proximal to the iliac vessel crossing, requiring stenting in preparation for secondary ureterorenoscopy (URS) were randomized to standard ureteric stenting or a suture stent. Secondary ureterorenoscopy was performed 2-6 weeks later. The Ureteral Stent Symptoms Questionnaire (USSQ) was completed after 1 week, on the day before URS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…11,25,26 In recent studies including randomization and patient blinding, the results confirmed that suture stent like JFil ® significantly improved patient comfort. 27,28 About one third of the patients in our study were fitted with these innovative stents. The top priority for future stents suitable for malignant diseases should be to integrate the importance of stent stiffness and shape according to the data of our current knowledge.…”
Section: Dovepressmentioning
confidence: 99%
“…11,25,26 In recent studies including randomization and patient blinding, the results confirmed that suture stent like JFil ® significantly improved patient comfort. 27,28 About one third of the patients in our study were fitted with these innovative stents. The top priority for future stents suitable for malignant diseases should be to integrate the importance of stent stiffness and shape according to the data of our current knowledge.…”
Section: Dovepressmentioning
confidence: 99%
“…2,3 The pigtail-suture stent (JFil ® or MiniJFil ® ) was developed as a means of decreasing urinary symptoms. 4,5 Fortuitously, we discovered that the sutures had surprising properties, and a clear dilation of the ureter without inflammation was observed around the suture. 4 However, the mechanisms involved in the ureteral dilation are still unknown.…”
Section: Introductionmentioning
confidence: 97%
“…Gli1 is the primary target of Hedgehog pathway activation and serves as a reliable indicator of Hedgehog signaling. 5 The authors were interested in Shh signaling because inactivating Shh in the mouse fetus resulted in hydroureter and overall aperistalsis. 8 Moreover, Shh signaling was important in regulating injury repair and wound healing after tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors for colonized bacteriuria are longer indwelling time of the ureteral stent, diabetes, female sex, chronic renal failure, diabetic nephropathy, and cancer, among which the indwelling time of the stent is the only changeable risk factor [17][18][19] . Currently, there are many strategies for ureteral stent, including stent coating [20] , surface modi cation [21] , reduction of stent materials [22] , and biodegradable stent [23] .…”
Section: Introductionmentioning
confidence: 99%